Vector analysis of astigmatic correction after small-incision lenticule extraction and femtosecond-assisted LASIK for low to moderate myopic astigmatism. Issue 4 (23rd July 2015) - Chan, Tommy C Y; Ng, Alex L K; Cheng, George P M; Wang, Zheng; Ye, Cong; Woo, Victor C P; Tham, Clement C Y; Jhanji, Vishal
Abstract : Aim: To compare astigmatic correction between femtosecond-assisted laser in situ keratomileusis (LASIK) and small-incision lenticule extraction (SMILE). Methods: A total of 111 patients were included in this prospective study. Fifty-seven eyes were treated with LASIK and 54 eyes were treated with SMILE for myopia with low to moderate (−0.25 to −4.0 D) astigmatism. Uncorrected distance visual acuity (UDVA), corrected distance visual acuity and manifest refraction were measured preoperatively and at 1 and 3 months postoperatively. Visual and refractive outcomes were reported. Changes in refractive astigmatism were evaluated using vector analysis. Results: Preoperative characteristics were similar between both groups. The UDVA at 1 and 3 months was better in the LASIK group compared with the SMILE group (p<0.009). Postoperative cylinder was higher in the SMILE group (p<0.001). Fewer eyes attained the attempted cylindrical correction in the SMILE group (p<0.029). Vector analysis showed no significant difference in target-induced astigmatism (p=0.091) and angle of error (p>0.596) between the two groups. Surgically induced astigmatism was significantly lower in the SMILE group (p<0.023), while the difference vector (p<0.001) and absolute angle of error (p<0.016) were significantly higher in the SMILE group. No significant difference was found in these parameters between 1 and 3 months in both groups (p>0.122). Conclusions: Our results showed that SMILE offered a less favourable astigmatic correction comparable to femtosecond-assisted LASIK in eyes with low to moderate myopic astigmatism. The alignment of treatment was more variable in SMILE, leading to a lower efficacy compared with LASIK by 3 months postoperatively.